Enhancing Dissolution of Ibuprofen via Solid Dispersion Using Hydrophilic Carrier and Fast Dissolving Sugars - Wedad Kamal Ali; Methaq Hamad Sabar; Athmar Dhahir Habeeb; Zainb Hassan Mahdi (College of Pharmacy / Mustansiriyah University, 2014)
In this study, solid dispersion using hydrophilic carriers (polyethylene glycols) and fast dissolving sugars (sorbitol and lactose) has been employed to enhance dissolution and hence the bioavailability of ibuprofen. Solid dispersions of different weight ratios (drug: carrier: fast dissolving sugars) have been prepared using fusion method. Microscopic images showed disappearance of specific features of ibuprofen, carriers and sugars in the solid dispersions. Release study of ibuprofen from prepared systems was performed in phosphate buffer pH 6.8; faster drug release was obtained from solid dispersions with high polyethylene glycol ratio and/ or from solid dispersions to which fast dissolving sugars has been added during their preparations. The study also explored hydrogen bond interactions between polyethylene glycols and ibuprofen in the solid dispersions. FTIR spectroscopy confirmed intermolecular interaction at (2:1) drug to carrier mole ratio. This interaction was considered the most important factor in enhancing the dissolution of ibuprofen via solid dispersions.